Perbedaan Perilaku Prososial Ditinjau Dari Tipe Kepribadian Ekstrovert Dan Introvert Pada Organisasi Berkah Langit Medan - Anna Wati Dewi Purba; Suci Ramadhani (Mahesa Research Center, 2021)
This study aims to see differences in volunteer prosocial behavior in terms of extrovert and introvert personality types in the heavenly blessing organization. Field. The sample in this study were 65 volunteers, so the hypothesis proposed in this study is that there are differences in prosocial behavior in terms of extrovert and introvert personality types, assuming extrovert personality types are more prosocial than introverted personality types. This research uses a scale of prosocial behavior which consists of 6 aspects, namely, sharing, cooperation (cooperating), helping, acting honestly (honesty), giving (donating), and paying attention to the welfare of others), and personality type scale. using screening to see personality types in organizational volunteers. Data collection was carried out using a Likert scale. Testing the proposed hypothesis is done using the technical analysis T-Test. Based on the results of the data analysis carried out, it was found that there were differences in prosocial behavior in terms of extrovert and introvert personality types. This result is known by looking at the value of the difference in the T-Test = 6.236 with P = 0.000 <0.05. This means that the hypothesis proposed is accepted with the result that there are differences in prosocial behavior in terms of extrovert and introvert personality types.